Improving Indonesia’s Sharia Banking Performance Through Intellectual Capital Efficiency and Sharia Compliance - Nurcahyo, Satria Avianda; Ferdianto, Raditya; Kusumawati, Diah Ayu (UNISSULA, 2025)
This research aims to analyze improving sharia banking performance, which has become the main focus for sharia banks worldwide, including PT. Bank Syariah Indonesia in Semarang and Salatiga. It examines the role of intellectual capital efficiency and sharia compliance as mediating variables in improving sharia banking performance. The research methodology uses a quantitative approach through SEM PLS data collected by surveys using questionnaires. The research respondents were employees of PT Bank Syariah Indonesia in Semarang and Salatiga, with a total of 250 employees, consisting of 145 male and 105 female employees. The sampling technique used was a census, where the entire population was directly sampled, so the number of respondents was 250. The results of the analysis show that intellectual capital efficiency and sharia compliance have a significant influence on increasing sharia banking performance at PT. Bank Syariah Indonesia in Semarang and Salatiga. Sharia compliance has also been proven to be a mediating variable influencing intellectual capital efficiency and banking performance. This research provides a deeper understanding of the relationship between intellectual capital efficiency, sharia compliance, and increasing sharia banking performance in the context of Islamic banks in Indonesia. The implications of this research can help bank management identify areas that need improvement and optimize resources to improve their overall performance. By increasing the efficiency of intellectual capital management and ensuring compliance with sharia principles, PT. Bank Syariah Indonesia in Semarang and Salatiga improved its overall performance and strengthened the trust of customers and other stakeholders.